Immunomodulatory effects of tricalcium silicate-based cements on osteogenesis. (September 2021) - Wan, Qian-Qian; Sun, Jin-Long; Ma, Yu-Xuan; Noble, Luke C.; Dong, Yan; Feng, Zhi-Hong; Gu, Jun-Ting; Wang, Yi-Rong; Wang, Wan-Rong; Bergeron, Brian E.; Jiao, Kai; Tay, Franklin R.; et al.
Highlights: TSCs can play an immunomodulatory role when implanted. TSCs induced M2 polarisation of macrophages. M2 polarised macrophages secreted cytokines to enhance bone regeneration. TSCs may be used to orchestrate crosstalk between immune response and tissue regeneration. Abstract: Although the effects of tricalcium silicate-based cements (TSCs) on osteogenesis have been extensively investigated, their immunomodulatory role on bone regeneration remains elusive. The present study investigated how TSCs modulate bone regeneration by inducing macrophage polarization. The ex vivo part of the study evaluated the effects of two TSCs on mouse bone marrow-derived macrophages (mBMDMs), and on the osteogenic potential of mouse bone marrow mesenchymal stromal cells (mBMMSCs) that had been co-cultured with TSC-exposed mBMDMs. The in vivo part of the study utilized a rat mandibular defect model to investigate the osteogenic effects of the TSCs on healing of bone defects. Immunofluorescence and immunohistochemistry were used to identify polarization of the macrophages adjacent to bone defects and their cytokine secretion in vivo . The TSCs induced mBMDMs to polarize into the M2 phenotype ex vivo . Osteogenic differentiation of mBMMSCs was enhanced when these cells were co-cultured with mBMDMs that had been exposed to either TSC at non-cytotoxic concentrations. In vivo observations of more profuse new bone formation, presence of defect-adjacent macrophages with M2 phenotype and expression of osteogenesis-related cytokines are indicative of the immunomodulatory role played by TSCs on bone regeneration. This is achieved via induction of macrophage polarization into the M2 phenotype. Graphical abstract: Image, graphical abstract